2014
DOI: 10.1387/ijdb.140084ss
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the wnt gene complement in a spiral-cleaving embryo and trochophore larva

Abstract: The highly conserved wnt gene family has roles in developmental processes ranging from axis formation to cell fate determination. The polychaete Platynereis dumerilii has retained 12 of the 13 ancient wnt subfamilies and is a good model system to study the roles of the wnt ligands in spiralian development. While it has been shown that Platynereis uses a global b-cateninmediated binary cell fate specification module in development, the early roles of the 12 wnt genes present in Platynereis are unknown. Transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 31 publications
2
52
1
Order By: Relevance
“…This is in contrast with another annelid, Hydroides, where MAPK appears to be activated only in the 4d cell, though the function of MAPK in that system has not been determined (Lambert and Nagy, 2003). We are just beginning to understand the molecular level events that control the processes of cell fate and axis specification during spiralian development (see papers by Gharbiah et al, 2014, Pruitt et al, 2014 …”
Section: The D Quadrant Organizermentioning
confidence: 99%
“…This is in contrast with another annelid, Hydroides, where MAPK appears to be activated only in the 4d cell, though the function of MAPK in that system has not been determined (Lambert and Nagy, 2003). We are just beginning to understand the molecular level events that control the processes of cell fate and axis specification during spiralian development (see papers by Gharbiah et al, 2014, Pruitt et al, 2014 …”
Section: The D Quadrant Organizermentioning
confidence: 99%
“…Whether localized extracellular Wnt ligands and polarized intracellular cortical components also play a role is currently unknown. A recent analysis of the expression patterns of the Wnt ligands in the embryo of Platynereis revealed that none of them seem expressed in the right place at the right time to act as a global regulator of β‐catenin asymmetries, suggesting a possible Wnt ligand independent mechanism in this organism …”
Section: Generation Of β‐Catenin Asymmetriesmentioning
confidence: 99%
“…(Irvine & Martindale, ), Helobdella sp. (Kourakis & Martindale, ; Kourakis et al, ), and Tubifex tubifex (Endo, Sakai, & Shimizu, ); the Wnt gene family, which has been studied in annelids in the context of body plan evolution (Cho, Vallès, Giani, Seaver, & Weisblat, ; Prud'homme, Lartillot, Balavoine, Adoutte, & Vervoort, ) and development (Demilly, Steinmetz, Gazave, Marchand, & Vervoort, ; Pruitt, Letcher, Chou, Bastin, & Schneider, ), particularly in relation to segmentation (Janssen et al, ; Prud'homme et al, ; Seaver & Kaneshige, ); and a set of genes used as putative stem‐cell markers in the germ line which includes, among others, vasa , piwi , and nanos (Ewen‐Campen, Schwager, & Extavour, ). Briefly, vasa encodes an ATP‐dependent RNA helicase that acts, among others, on nanos , which suppresses somatic differentiation, and piwi encodes a regulatory protein with RNase H endonuclease activity that plays an important role in cell stemness (Extavour & Akam, ; Gustafson & Wessel, ; Rebscher, ; van Wolfswinkel, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, other annelids have been also subjected to molecular developmental studies in order to address questions such as the development of body plans, the regeneration of lost parts, the differentiation of Primordial Germ Cells (PGCs), the establishment of gonads, and the proliferation of somatic tissues. Among the most widely investigated genes related to these questions are the Hox genes, for which whole-body expression patterns have been characterized for body plan evolution (Cho, Vallès, Giani, Seaver, & Weisblat, 2010;Prud'homme, Lartillot, Balavoine, Adoutte, & Vervoort, 2002) and development (Demilly, Steinmetz, Gazave, Marchand, & Vervoort, 2013;Pruitt, Letcher, Chou, Bastin, & Schneider, 2014), particularly in relation to segmentation (Janssen et al, 2010;Prud'homme et al, 2003;Seaver & Kaneshige, 2006); and a set of genes used as putative stem-cell markers in the germ line which includes, among others, vasa, piwi, and nanos (Ewen-Campen, Schwager, & Extavour, 2010). Briefly, vasa encodes an ATP-dependent RNA helicase that acts, among others, on nanos, which suppresses somatic differentiation, and piwi encodes a regulatory protein with RNase H endonuclease activity that plays an important role in cell stemness (Extavour & Akam, 2003;Gustafson & Wessel, 2010;Rebscher, 2014;van Wolfswinkel, 2014).…”
Section: Introductionmentioning
confidence: 99%